Self-Talk to Improve Body Image Satisfaction Among Female Students in Junior High School - Anugrah Fadlilah Al Islami; Dian Fitriani; Nurwahyuni Nurwahyuni; Hasan Hasan (FKIP - Universitas Riau, 2026)
Many female students are dissatisfied with their physical appearance, so they often avoid activities that involve physical appearance. This study aims to identify the effectiveness of self-talk techniques in improving body image satisfaction among female students at SMP Negeri 9 Palu. The subjects in this study were 8 female students. The data collection technique in this study was the Multidimensional Body Self Relation Questionnaire-Appearance Scale (MBSRQ-AS). The data obtained were processed and analyzed using descriptive and inferential methods with the Wilcoxon Sign Rank Test formula. Descriptive analysis results showed that before the provision of group counseling services using self-talk techniques, there were 8 female students with low body image satisfaction classification. After the provision of group counseling services using self-talk techniques, there were 7 female students with high body image satisfaction classification and 1 female student with very high body image satisfaction classification. The inferential analysis results showed that the Asymp. Sig. (2-tailed) value was 0.012, which is smaller than 0.05 (0.012<0.05). This proves that the provision of group counseling services using self-talk techniques can increase body image satisfaction among female students at SMP Negeri 9 Palu.